A comparison of some blood values of trainers of the boxing national team before and after boxing matches - Pala, Ragıp; Çınar, Vedat; Kılıç, Yakup; Karadağ, Mustafa (My University, 2012)
Purpose: This study was materialized with the aim to determine in what extend the glucose, insulin, cortisol, and creatine levels of the Turkish Boxing National Team Trainers was effected before and after the matches which were fought during the European Boxing Championship. Materials-Methods: This research was materialized on the trainers of the national boxing team who were on charge during the world boxing championship for women, held in Istanbul in the year 2011. Blood was obtained before and after the matches from all the subjects, and their glucose, insulin, cortisol, and creatine levels were analyzed. The blood samples were analyzed at the Animal Feeding laboratory of the Faculty of Veterinary Science, Firat University. Symptoms: In accordance with the data derived before the match and after the match, the glucose level was significantly reduced when compared with the measures taken before the match (p<0.05). After the application, there was no significant difference observed between the blood values which were obtained after the match with pre-test measures and post-test measures, for checking the insulin level (p>0.05). There was statistically a significant increase in the post-test measurements of the cortisol values when compared with the data derived from the pre-test measurement (p>0.05). There was no significant difference between the measurements with regard to creatine (p>0.05). Conclusions: It’s proposed in accordance with the results of the study that, changes have been occurred between the measurements of the trainers of the boxing national team with regards to glucose and cortisol.
Boks milli takım antrenörlerinin maç öncesi ve maç sonrası bezı kan değerlerinin karşılaştırılması
Bildiri - Yayımlanmış
Keywords: Boks; Match; Blod parameters; Maç; Kan parametreleri